The leadership of The Head of Madrasah in Developing The Quality of Education - Rofik, A.; Siswanto, Romi (Chalim Journal of Teaching and Learning, 2023)
The education of the island community is very complex with various problems. Island communities still do not pay full attention to the world of education. The development of the quality of education in madrasahs or island schools must be the mainstream of the education recovery movement, including in MTs Nurul Huda. This study examines the quality of education with the type of research that the author uses in this study is qualitative field research (field Research). Research has produced an analysis that illustrates the leadership of MTs. principal Nurul Huda uses a Transformational leadership model, an Individual and Collective Leadership Model; has leadership modalities in the form of knowledge (Cultural), network (Symbolic), and economic (Financial); and has a leadership contribution in developing the quality of education Field of Institutional Management, Field of Education Quality Management. With the model and modality used by MTs. principal Nurul Huda is able to implement and implement national education standards well and develop quality-based education.